Analisis RTOP untuk Mengajarkan Keterampilan Scientific Communication pada Calon Guru dengan Pendekatan STEM-SDGs - Annisa Dzikro Afifah (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
In one of the high schools in the Jember Regency, the focus of education is more on mastering concepts rather than on scientific communication skills. The lack of teacher proficiency in scientific communication skills has a direct impact on the suboptimal mastery of students. To assess the teaching capabilities, an analysis of the RTOP (Reform Teaching Observation Protocol) instrument with a STEM-SDGs approach was conducted to teach scientific communication skills. In this study, the researcher utilized EFA (Exploratory Factor Analysis) and reliability testing using Cronbach’s α with the assistance of SPSS 26. The results of this research revealed four valid and reliable factors, comprising a total of 14 RTOP items. The RTOP instrument can be employed by educators to assess teaching capabilities in the realm of scientific communication skills with a STEM-SDGs approach. Based on the conducted research, improvements in RTOP validity and reliability testing were identified. The RTOP instrument, coupled with the STEM-SDGs approach, consistently measures teaching capabilities related to scientific communication skills.
Entry oleh Arif 2026 Maret 05
Keywords: RTOP; Scientific communication; STEM-SDGs